The Language of Companionship: A Critical Stylistic Examination of True and False Friendship in Niyi Osundare’s Poetry - OSENI, Abdullateef Babatunde (Educalingua Journal, 2025)
Friendship, a central theme in human relationships, has been a subject of poetic exploration across cultures. Niyi Osundare, a renowned Nigerian poet, examines the dual nature of friendship in his poems Friendship Blue, One Side and Friendship Blue, Another Side from the collection Random Blues. This study employs the Critical Stylistics (CS) approach, developed by Jeffries (2010), to analyse how Osundare’s linguistic and stylistic choices shape the representation of false and true friendship. This research uncovers the ideological underpinnings of these poems by examining Osundare’s use of naming and description, representing actions/events/states, and comparing and contrasting. Through qualitative textual analysis, the study investigates how language constructs opposing depictions of deceptive and genuine friendships. Findings reveal that Friendship Blue, One Side employs negative imagery, contrasting metaphors, and descriptive language to depict false friends as exploitative and deceitful. Conversely, Friendship Blue, another side, portrays true friends using positive and valuable imagery, emphasising trust and loyalty. The study highlights how Osundare’s poetic style not only critiques hypocrisy in relationships but also celebrates sincere companionship. The conclusion affirms that linguistic choices in poetry are potent tools for ideological expression, allowing Osundare to influence readers' perception of friendship. This research contributes to Critical Stylistics and African poetry studies by demonstrating the effectiveness of CS tools in uncovering deep-seated ideologies within poetic texts. It also provides insights into how language shapes human relationships in literature.